2017
DOI: 10.1002/chem.201701301
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I)‐Catalysed Asymmetric Hydroamination of Alkenes: A Silver‐ and Solvent‐Dependent Enantiodivergent Reaction

Abstract: In the present study, we report the first silver-dependent enantiodivergent gold-catalysed reaction. The asymmetric intramolecular hydroamination of alkenes catalysed by the combination of a single chiral binuclear gold(I) chloride complex and silver perchlorate can afford both enantiomers of the products by a simple solvent change from toluene to methanol. Such an enantiodivergent reaction is strictly independent of the reaction temperature or of the nature of the catalyst anion and displays the same first-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 200 publications
3
23
0
Order By: Relevance
“…Many more synthetic efforts have been made in this area with gold(I)-phosphine complexes. Michon and Agbossou-Niedercorn investigated intramolecular hydroamination of alkenes in details, and better enantioselectivity were obtained in the case of bisphosphine ligand 170 [115,119,120]. The authors also observed a rare dependence of configuration of newly formed stereogenic center on the presence of silver salt [120].…”
Section: Furan Pyrrolidine and Indanone Derivativesmentioning
confidence: 98%
“…Many more synthetic efforts have been made in this area with gold(I)-phosphine complexes. Michon and Agbossou-Niedercorn investigated intramolecular hydroamination of alkenes in details, and better enantioselectivity were obtained in the case of bisphosphine ligand 170 [115,119,120]. The authors also observed a rare dependence of configuration of newly formed stereogenic center on the presence of silver salt [120].…”
Section: Furan Pyrrolidine and Indanone Derivativesmentioning
confidence: 98%
“…29 However, these specific substrate-metal complex interactions have not been observed to result in a complete reversal of enantioselectivity depending on the choice of metal catalyst. While a number of previous reports [6][7][8][9][14][15] have observed metal-dependent enantiodivergence, reliance on an additional Lewis basic site of the reactive substrate has not previously been suggested as a rationale for such a reversal. In this system, the choice of metal influences the coordination environment of the metal-ligand complex while the active participation of a Lewis basic site in the substrate is critical to induce the observed reversal of enantioselectivity.…”
Section: Figure 11mentioning
confidence: 99%
“…Several reports observing a reversal in enantioselectivity with the same chiral source exist, including the use of distinct metals, 6 counterions, 7 the introduction of subtle structural modifications of the catalyst system, 8 or simply changes in solvent or temperature. 9 Nevertheless, the design of effective and general catalytic asymmetric methods to induce complete reversals in enantioselectivity continues to be a challenge. 5e,f Importantly, often only one of the two enantiomers is obtained in high enantiomeric excess since it is difficult to induce large energy differences between transition states that lead to the competing products required for effective enantiodivergence.…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of organometallic and coordination complexes containing an Au-F bond is underdeveloped, with only 8 unique compounds for Au( I) [1][2][3][4][5][6] and 15 for Au(III) [7][8][9][10][11][12][13][14][15][16] as well as a single Au(II) complex 17 having been characterized by X-ray crystallography. The first was described in 2005, with most examples being reported in the past 5 years as interest in the area increases.…”
Section: Introductionmentioning
confidence: 99%